KAJIAN MANAJEMEN OPTIMALISASI PENERANGAN JALAN UMUM KOTA SEMARANG - Aris Widodo (Jurnal Teknik Sipil dan Perencanaan)
This research mainly aims to give input to Semarang Local Government in the efficiency of electricity utilization to the street illumination and the management of income tax from the societies, so they can be utilized optimally, directly, and in integrated way in order to the management of city infrastructures service. This research using the influence of traffic passenger car unit (pcu) for optimizing in a low density of traffic condition. The data of the Average Daily Traffic (ADT) volume on Pahlawan street was gathered from 6.00 p.m-6.00 a.m in every 15 minutes. The data was analyzed using quartile technique with K1 (25%) and K2 (50 %), then the researcher designed a line chart table of a link between the ADT and the time of the electricity switching on. In working days, the results are (1) the efficient time of street illumination in K1 (25%) was between 10.30 p.m-3.45 a.m, (2) in K2 (50%) was between 9.45 p.m-4.30 a.m. Due to the security and the beauty of the town and also considering the density of the traffic, the optimization and the dimming of the electricity are not needed in holidays. The optimization using ballast dimming (40%) from 250 watt to 150 watt for all lamps, obtained a significant account 32,4 Lx for average illumination. It is still fulfill the minimal requirement of 7 Lx for the average illumination on the collector street type. The optimization with dimming system obtained an efficiency in K1 (25%) was 23.16% and in K2 (50%) was 25,05%.